2018
DOI: 10.1093/toxsci/kfy272
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate Ameliorates Cardiac Dysfunction Caused by Ischemic Insults Through AMPK Signal Pathway—Not Only Shifts Metabolism

Abstract: Dichloroacetate (DCA), an inhibitor of pyruvate dehydrogenase kinase (PDK), regulates substrate metabolism in the heart. AMP-activated protein kinase (AMPK) is an age-related energy sensor that protects the heart from ischemic injury. This study aims to investigate whether DCA can protect the heart from ischemic injury through the AMPK signaling pathway. Young (3-4 months) and aged (20-24 months) male C57BL/6J mice were subjected to ligation of the left anterior descending coronary artery (LAD) for an in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…It must be taken into account that DCA can target other cellular pathways in addition to PDK. Indeed, it has been reported that DCA affects the CoA biosynthetic pathway [42], activates the AMPK signaling pathway [43], antagonizes with acetate [44], and disturbs the tyrosine catabolism [45]. Moreover, comparison of the metabolite profiles in cells treated with DCA or more selective novel inhibitors of PDK resulted in different outcomes [46].…”
Section: Discussionmentioning
confidence: 99%
“…It must be taken into account that DCA can target other cellular pathways in addition to PDK. Indeed, it has been reported that DCA affects the CoA biosynthetic pathway [42], activates the AMPK signaling pathway [43], antagonizes with acetate [44], and disturbs the tyrosine catabolism [45]. Moreover, comparison of the metabolite profiles in cells treated with DCA or more selective novel inhibitors of PDK resulted in different outcomes [46].…”
Section: Discussionmentioning
confidence: 99%
“…DCA is known to be neurotoxic when high doses, above 500 mg/kg, are used, or if 300 mg/kg is administered for more than 10 weeks [73,74]. However, many previous animal studies have confirmed the beneficial effects of administering DCA at dose of 50 to 200 mg/kg [75,76,77,78,79], and our previous study also confirmed that treatment with a dose of 100 mg/kg after ischemia reduced neuronal death [26]. According to the paper by Stacpoole, it was noted that DCA was rapidly absorbed following treatment, crosses the blood-brain barrier and activates PDH within a few minutes [80].…”
Section: Discussionmentioning
confidence: 99%
“…The concept that the activation of AMPK is beneficial to various diseases has been widely recognized [56][57][58]. It has been proved that activating AMPK can improve cardiometabolic disease [7], protect from myocardial ischemia [7], inhibit cardiac hypertrophy and cardiomyopathy [8,[59][60][61], protect heart function and delay heart failure [7,[62][63][64][65], and antiarrhythmia [10]. Additionally, the decreased activity of AMPK has also been shown to participate in hypertension [48,66], lipid metabolism, inflammation [58], obesity, insulin resistance, type 2 diabetes [67], renal pathophysiology, aging [68], and tumor [68,69].…”
mentioning
confidence: 99%